PENDIDIKAN ISLAM DAN ALIRAN FILSAFAT PENDIDIKAN REKONSTRUKSIONISME - Qomariyah, Nurul (STAI AL FALAH Banjarbaru, 2017)
Philosophy is thinking, asking, love, wisdom and many other meanings of others. While Islamic Education Philosophy is systematic and radical philosophical thoughts, taken from the philosophical system or philosophical answer to the problem of education, which can be used as a guide for the educational process based on Islamic teachings. Reconstruction of one of the modern schools of education The flow of reconstructionism argues that the task of saving the world is the duty of all humanity or nation. Therefore it is necessary to re-foster healthy intellectual and spiritual power through proper education of true values and norms for the present and future generations, thus forming a new world in the control of mankind. Keywords: Philosophy, Education, Reconstructionism